fMRI neurofeedback in emotion regulation: a literature review - Linhartová, Pavla; Látalová, Adéla; Kóša, Barbora; Kašpárek, Tomáš; Schmahl, Christian; Paret, Christian (NeuroImage, 2019)
Objectives - Emotion regulation is one of the most prevalent objectives for real-time fMRI neurofeedback (rt-fMRI-NF) studies. The existing studies differ in a number of methodological parameters. This study provides a literature review of the main parameters and results of studies using rt-fMRI-NF for emotion regulation enhancement. - Method - A search of the Web of Science database up through November 8, 2018, identified 144 articles written in English, 89 of which were excluded as irrelevant for this study. The remaining 51 original studies and four secondary analyses of previously published original studies were included in the literature review. The selection of target brain areas, target populations, emotion regulation protocols, NF presentation, control group types, and emotion regulation instructions were examined in relation to achieved brain regulation and changes in cognitive or clinical outcomes. Study results were evaluated in terms of their statistical robustness. - Results - The results show that healthy people are able to regulate their brain activity in the presence of rt-fMRI-NF from various brain regions related to emotion regulation, including the amygdala, anterior insula, and anterior cingulate cortex. The regulation of brain activity using rt-fMRI-NF from prefrontal-limbic connectivity or from individually navigated brain areas is feasible as well. Most studies that used a control group show that rt-fMRI-NF actually induces some effects on brain regulation, cognitive variables, and clinical variables. Generally, the success of ROI regulation during NF training is related to the combination of target brain region, the type of emotion regulation task, and the population undergoing the training. In terms of patient groups, the strongest support for the beneficial effects of rt-fMRI-NF has been shown in increased positive emotion experiencing in patients with depression and in decreased anxiety in patients with anxiety disorders. Symptom reduction following NF training has been also reported in patients with PTSD, BPD, and schizophrenia, but direct comparisons with control groups in these studies makes it impossible to evaluate the added value of NF. Studies often do not report all the relevant analyses for evaluating NF success and many studies lack statistical robustness. - Conclusions - Overall, rt-fMRI-NF seems a promising tool for emotion regulation enhancement with the potential to induce long-term symptom reduction in patients with various mental disorders. Preplanning of statistical analyses, careful interpretations of the results, and evaluations of the NF effect on symptom reduction in patient groups is recommended.